The girl on the train - Hawkins, Paula (New York : Riverhead Books, a member of Penguin Group (USA), 2015)
Obsessively watching a breakfasting couple every day to escape the pain of her losses, Rachel witnesses a shocking event that inextricably entangles her in the lives of strangers.
Keywords: Railroad travel -- Fiction; Commuters -- Fiction; Strangers -- Fiction; London (England) -- Fiction; Psychological fiction; Suspense fiction